2010
DOI: 10.1021/ie1008794
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chromium(VI) from Aqueous Solutions Using Polyaniline Doped with Sulfuric Acid

Abstract: A type of polyaniline was synthesized and its Cr (VI) removal potential was investigated in this work. The kinetics study, adsorption isotherm, pH effect, and thermodynamic study were examined in batch experiments. Adsorption data for Cr (VI) uptake by polyaniline were analyzed according to Langmuir and Freundlich adsorption models. Thermodynamic parameters for the adsorption system were determinated at 293 K, 303 K, and 313 K (ΔH° = 23.87 kJ mol−1; ΔG° = −10.76 to −13.13 kJ mol−1 and ΔS° = 118.20 J K−1 mol−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(46 citation statements)
references
References 31 publications
1
41
0
2
Order By: Relevance
“…The increase in the amount of the PPy/Fe 3 O 4 nanocomposite is significantly influenced the extent of adsorption due to the increase in the number of active sites available for adsorption. In similar studies to explore the effect of adsorbent dose on Cr(VI) removal, Zhang et al using polyaniline doped with sulfuric acid found that 4 g/L was required to achieve 100% removal of Cr(VI) from aqueous solution containing 50 mg/L [45]. Ansari and Fahim [34] used up to 24 g/L of polypyrrole coated on wood sawdust to achieve 100% removal of Cr(VI) from a solution initially containing 100 mg/L while to effect a 100% removal of Cr(VI) from a solution containing only 3 mg/L, Hu et al [46] found that 1.4 g/L of oxidized multiwalled carbon nanotubes was required.…”
Section: Effect Of Adsorbent Dosementioning
confidence: 99%
“…The increase in the amount of the PPy/Fe 3 O 4 nanocomposite is significantly influenced the extent of adsorption due to the increase in the number of active sites available for adsorption. In similar studies to explore the effect of adsorbent dose on Cr(VI) removal, Zhang et al using polyaniline doped with sulfuric acid found that 4 g/L was required to achieve 100% removal of Cr(VI) from aqueous solution containing 50 mg/L [45]. Ansari and Fahim [34] used up to 24 g/L of polypyrrole coated on wood sawdust to achieve 100% removal of Cr(VI) from a solution initially containing 100 mg/L while to effect a 100% removal of Cr(VI) from a solution containing only 3 mg/L, Hu et al [46] found that 1.4 g/L of oxidized multiwalled carbon nanotubes was required.…”
Section: Effect Of Adsorbent Dosementioning
confidence: 99%
“…Many groups have reported the removal of toxic Cr(VI) by PANI and PANI-based composite materials [36][37][38][39]. According to these reports, the removal of Cr(VI) is due to the reduction of Cr(VI) to Cr(III) by PANI.…”
Section: Introductionmentioning
confidence: 99%
“…The Cr (III) can be further adsorbed on the surface of PANI-G10 and chelated with imino groups [15].…”
Section: Mechanism Of Cr (Vi) Adsorptionmentioning
confidence: 99%